Does transhumant sheep system provide ecosystem services for climate change adaptation in Mediterranean environment? - Francioni M.; Toderi M.; Lai R.; Trozzo L.; Foresi L.; Sciarra F.; Avanzolini P.; Sedic E.; Budimir K.; Santilocchi R.; D'Ottavio P. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Since adaptation to climate changes has become a major challenge for the scientific communities, provisioning Ecosystem Services as Climate Regulation are growing in research interest. Greenhouse gasses are widely considered drivers of climate change and it has been demonstrated how different agro-ecosystems can influence the climate by either taking or realising greenhouse gases. Land use change does affect the soil C pool and many authors showed how the conversion of permanent vegetation (forests or grasslands) to cultivated crops led to a loss of soil C. On the contrary, many researches highlighted how croplands re-converted in grasslands ensure a soil C increment. Central Italy cropping system is characterised by rainfed winter cereals in rotation with preparative crops in the hilly areas and with high value crops (mainly, horticultural crops or vegetables) in the river valleys. Within this system, the presence of transhumant sheep farms allowed the conversion of annual crops in long lasting alfalfa grasslands (up to 10 years) grazed by flocks during the winter period. In this paper, we compared two conventional crop fields with a five-years lasting alfalfa grassland analysing heterotrophic soil respiration effluxes and soil C stock. Results suggest that transhumant system is able to increase the soil C sequestration.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)